2018
DOI: 10.1016/j.ijid.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of candidaemia in a nationwide cohort: Underlying diseases, risk factors and mortality

Abstract: A substantial prevalence of multi-morbidity and a high 30-day mortality was found. We hypothesise, that an increasing population of severely ill patients with prolonged supportive treatment and microbiological testing may in part explain the high candidaemia incidence in Denmark. Nationwide studies are warranted to clarify this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 32 publications
13
20
0
Order By: Relevance
“…The use of echinocandins has increased as an initial therapy for candidaemia during the same period, and it might have decreased the mortality rate. The overall 30‐day mortality rate was similar to figures reported in other Nordic countries: Iceland (30%, 2013), Norway (36%, 2019) and Denmark (37%, 2011 and 43%, 2018) 5,29,31,36 . The 30‐day mortality was 20.0% in PC and 13.9% in non‐PC in our study, but the difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The use of echinocandins has increased as an initial therapy for candidaemia during the same period, and it might have decreased the mortality rate. The overall 30‐day mortality rate was similar to figures reported in other Nordic countries: Iceland (30%, 2013), Norway (36%, 2019) and Denmark (37%, 2011 and 43%, 2018) 5,29,31,36 . The 30‐day mortality was 20.0% in PC and 13.9% in non‐PC in our study, but the difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 78%
“…The 30‐day mortality was 20.0% in PC and 13.9% in non‐PC in our study, but the difference did not reach statistical significance. Surprisingly, the overall 30‐day mortality rate was lower in PC than overall in our hospital district or in general in candidaemia 2‐5 . Candidaemia is associated with severe underlying comorbidities, for example malignancies 36 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the previous studies, mortality rates of approximately 28% have been described, compared with 5% in our cohort . These high mortality rates are often reported in critically ill patients on intensive care units, whereas chronic IF patients tend to be more healthy and live in a relative stable condition at home . Of note, it is unlikely that virulence of certain Candida species played a role, as the distribution of cultured species was similar to other studies …”
Section: Discussionsupporting
confidence: 82%
“…6 These high mortality rates are often reported in critically ill patients on intensive care units, whereas chronic IF patients tend to be more healthy and live in a relative stable condition at home. 23 Of note, it is unlikely that virulence of certain Candida species played a role, as the distribution of cultured species was similar to other studies. 5,8,9 Plantinga et al previously reported in healthy volunteers having 3 TLR1 SNPs a significantly decreased expression of IL-1β, IL-6, and IL-8.…”
Section: Discussionsupporting
confidence: 76%